Education and the Love for the World: articulating a post-critical educational philosophy - Naomi Hodgson; Joris Vlieghe; Piotr Zamojski (FahrenHouse, 2018)
Sharing with critical pedagogy the belief that there is no necessity in the given order of things, and that we can always begin anew with the world, the post-critical educational philosophy articulated here seeks to overcome the internal contradictions of this paradigm by positing an affirmative, educational approach to educational philosophy. This understands education not as political action, as in critical pedagogy, working in the name of emancipation, but rather, following Rancière, assumes an equality of intelligences as a starting point from which the world can be set free for the new generation. This entails a pedagogy founded on an attitude of unconditional love both of the world and of the new generation, in the Arendtian sense. In this article we formulate a set of principles that articulate what such an affirmative attitude consists of: striving for pedagogical hermeneutics (rather than defending a hermeneutical pedagogy); adhering to a principled normativity (rather than to a procedural one); taking education to be for education's sake (rather than for extrinsic goals such as global citizenship); and starting from a passionate devotion to what is good in the 'here and now' (rather than by a hatred of the world in expectation of a utopia that is never to come).